STRATEGI PENINGKATAN KINERJA P3A PADA DAERAH IRIGASI BELITANG II DI JARINGAN TERSIER DI KABUPATEN OKU TIMUR PROVINSI SUMATERA SELATAN - , Hassadunin, SP; , Prof. Dr.Ir.Fatchan Nurrochmad, M.Agr. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Farmers' Water User Association (P3A) has objective to utilize the potential of available tertiary irrigation water to increase the farmers' welfare. For that purpose, the institutional performance is a success key in managing the tertiary irrigation networks located in Belitang II Eastern OKU District. The primary data was collected from P3A questionnaire which was used to assess the performance of institutional , financial, technical aspects and secondary data was the data of Regional Irrigation Belitang II. The P3A performance on tertiary irrigation network management was done by correlation test and analysis. P3A performance in tertiary network was analyzed by using SWOT. The current P3A condition has not fulfilled the entire farmers demands, and the preliminary observations found that P3A does not have a solid institutional structure due to their uncoordinated activities. Although, P3A has not satisfied the farmers' expectations, but it is legitimated with the board legality and having an intensive communication as well as household budget to support government policy. The study suggests some strategies to improve the institutional performance through the SWOT analysis, which are improving farmersâ human resource, building inspection channel, optimizing cooperation of government and P3A in participatory irrigation management, increasing farmersâ economy, to optimize the access to the bank on equal opportunity. The study also suggests that settlement of internal organizational conflicts and intensification pattern should be conducted through agricultural technology optimization solutions and the optimization routine of tertiary network should be directed to maintain the food sector.